Regulation of the Movement of Workers: Forced Labor in the United States - Ivan C. Rutledge (Washington University Law Quarterly, 1953)
The extent of freedom to migrate for employment and the legal protection accorded to it are explored as they relate to migration within the boundaries of the United States. The purpose of this essay is to describe the basic constitutional norms to which controls upon internal movement of workers must conform and to provide a measuring-rod for calculation of policy concerning supplementation of the labor force from abroad.
Keywords: Labor law; Slavery